Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing (Studi Kasus Pada Usaha Konveksi “Mowin Concept”) - Nurul Afifah; Arwan Gunawan (Indonesian Accounting Literacy Journal, 2020)
Determination of the cost of goods manufactured can be the basis for determining the selling price. Companies usually lack detail in identifying factory overhead costs, which will result in companies not knowing for sure the profit it receives. This research was conducted at business convection Mowin Concept. They aren’t included all elements of factory overhead costs so that the cost of goods manufactured isn’t correct. The purpose of this research is to determine the calculation of the cost of goods manufactured using the job order costing method in a case study of ordering 300 sets of prison uniforms. The result of this study that calculating the cost of goods manufactured according to the company is Rp47.007/unit, so the selling price is Rp65.000. Meanwhile, the calculation uses the job order costing method is Rp51.319/unit, so the selling price is Rp70.900. There was a 9.17% increase in the cost of goods manufactured and a 9.07% increase in the selling price. Therefore, the company should calculate all elements of factory overhead costs and use the job order costing method with the job order cost sheet.